2020
DOI: 10.1111/bcp.14229
|View full text |Cite
|
Sign up to set email alerts
|

A 3‐year prospective study of a multidisciplinary early proactive therapeutic drug monitoring programme of infliximab treatments in inflammatory bowel disease

Abstract: Aims: Therapeutic drug monitoring (TDM) of trough serum infliximab concentrations has been mainly used in case of loss of response in patients with inflammatory bowel disease (IBD). The aim of this study was to evaluate the effectiveness and safety of a multidisciplinary early proactive TDM (mep-TDM) programme for dose adjustment. Methods: A 3-year prospective study was conducted based on a sample of 81 patients who started treatment and were subsequently subjected to mep-TDM with the first control at week 14.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 46 publications
0
30
0
Order By: Relevance
“…2]. More recently, proactive TDM has been proposed as a tool to optimize initial drug treatment in these patients [4][5][6]. With proactive TDM, target TL are stipulated before induction and -when measured and found subtherapeutic (in the absence of ADA) during and after induction -the drug dose is progressively increased.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…2]. More recently, proactive TDM has been proposed as a tool to optimize initial drug treatment in these patients [4][5][6]. With proactive TDM, target TL are stipulated before induction and -when measured and found subtherapeutic (in the absence of ADA) during and after induction -the drug dose is progressively increased.…”
Section: Discussionmentioning
confidence: 99%
“…With proactive TDM, target TL are stipulated before induction and -when measured and found subtherapeutic (in the absence of ADA) during and after induction -the drug dose is progressively increased. A number of studies have indeed shown that this interesting strategy could reduce PNR incidence and improve long-term outcomes [4][5][6]. However, solid evidence for routine clinical use is still lacking [12,13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therapeutic drug monitoring (TDM) is an established method to facilitate concentration-guided dose adaption but requires significant clinical and analytical resources to quantify the drug of interest and establish a robust evidence base. To date, few cancer medicines have met the level of evidence required to implement TDM in a clinical setting [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%